A Four-Year Monocentric Study of the Complications of Third Molars Extractions under General Anesthesia: About 2112 Patients - A. Guerrouani; T. Zeinoun; C. Vervaet; W. Legrand (Hindawi Limited, 2013)
Introduction. The aim of this study was to assess the complications resulting from third molar extraction under general anesthesia. Material and Methods. The retrospective study included all patients who underwent impacted third molars extraction from January 2008 until December 2011. 7659 third molars were extracted for 2112 patients. Postoperative complications were retrieved from medical files. Results. No complications were related to general anesthesia. The most frequent postoperative complication was infection (7.15%). Lingual nerve injuries affected 1.8% of the patients. All of them were transient and were not related to tooth section. Inferior alveolar nerve injuries were reported in 0.4% of the cases. 95.8% of these patients were admitted for one-day ambulatory care, and only two patients were readmitted after discharge from hospital. Discussion. This surgical technique offers comfort for both surgeons and patients. Risks are only linked to the surgical procedure as we observed no complication resulting from general anesthesia. One-day hospitalization offers a good balance between comfort, security, and cost. The incidence of complications is in agreement with the literature data, especially regarding pain, edema, and infectious and nervous complications. It is of utmost importance to discuss indications with patients, and to provide them with clear information.